Nitrogen-doped porous carbon foams prepared from mesophase pitch through graphitic carbon nitride nanosheet templates1. Issue 57 (25th June 2015) - Xie, Rui-Lun; Zong, Zhi-Min; Liu, Fang-Jing; Wang, Yu-Gao; Yan, Hui-Long; Wei, Zhe-Hao; Mayyas, Mohannad; Wei, Xian-Yong
<x xml:space="preserve">Abstract</x> A scalable and facile method was developed to synthesize nitrogen-doped porous carbon foams (NPCFs) using graphitic carbon nitride (g-C3N4) nanosheets as hard templates through the calcination of mesophase pitch.